PESTICIDES AND AQUATIC ECOSYSTEMS
A survey made in West Bengal to evaluate the influence of pesticides on aqustic ecosystems showed that pesticides killed many fisheÂ» in Punarbbava River, West Danajpur, in August 1970. The paddy fields near the river received the insecticides: DDVP, phosphamidon and parathion. The tissues of gills, alimentary tract, liver and brain of the exposed carp Labeo rohita) and catfish Heteropneustes fossilis) were found severely damaged. The pesticide residue in fish was in such level that may cause hazard to fish eaters, number=1 & 2, journal=Indian Journal of Fisheries, author=Konar, S K, year=2011, month=Nov., pages=80–85